2015
DOI: 10.1038/bjc.2015.207
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16 in squamous cell carcinoma of the mobile tongue is independent of HPV infection despite presence of the HPV-receptor syndecan-1

Abstract: Background:Tongue squamous cell carcinoma (TSCC) is increasing in incidence, especially among young patients and preferably females. Infection with human papilloma virus (HPV) has been suggested as a cause of SCC in the head and neck, and the proportion of oropharyngeal cancers caused by HPV has steadily increased.Methods:Samples from 109 patients with primary TSCC were analysed for the presence of HPV16 by in situ hybridisation and for expression of its surrogate marker p16 and the HPV receptor syndecan-1 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 35 publications
8
34
2
Order By: Relevance
“…So far there is no explanation for this increase. Apart from showing higher recurrence rate in young patients, we have previously shown specific characteristics for young patients with TSCC such as higher levels of the podoplanin protein and worse prognosis when lacking expression of the p16 tumour suppressor protein . The former finding has implications for therapeutic use as there are antibodies available against podoplanin …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…So far there is no explanation for this increase. Apart from showing higher recurrence rate in young patients, we have previously shown specific characteristics for young patients with TSCC such as higher levels of the podoplanin protein and worse prognosis when lacking expression of the p16 tumour suppressor protein . The former finding has implications for therapeutic use as there are antibodies available against podoplanin …”
Section: Discussionsupporting
confidence: 88%
“…Apart from showing higher recurrence rate in young patients, 15 we have previously shown specific characteristics for young patients with TSCC such as higher levels of the podoplanin protein and worse prognosis when lacking expression of the p16 tumour suppressor protein. 16 The former finding has implications for therapeutic use as there are antibodies available against podoplanin. 17 When looking at the oncoprotein c-MYC, age did not seem to influence its levels in TSCC, whereas, in accordance with previous findings, 12 gender did, with females showing more low-expressing and males more high-expressing tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Lingen et al reported that the positive predictive value of p16 as a potential indicator of HPV status in the oral cavity was approximately 40% [18]. Sgaramella et al found no evidence of HPV 16 DNA in 71 SCCs of the tongue, whereas 36 of these 71 SCCs (51%) showed p16 staining [34]. Various mechanisms likely contribute to the poor concordance between p16 IHC and HPV ISH findings, including overlapping oral cavity/oropharyngeal disease whose epicenter in the oropharynx cannot be determined due to tumor size at presentation, true HPV-positive tumors that originate in reticular epithelium in oral cavity sites, and low sensitivity of the methods (particularly p16) in detection of the truly HPV-driven cases [18, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Patient characteristics are shown in Table . Tissue biopsies had been consecutively collected and some patients were included in our previous studies with different objectives . Biopsies taken from the lateral border of the tongue from 14 healthy volunteers not exposed to classic oral cancer risk factors (smoking and alcohol) had also been collected previously .…”
Section: Methodsmentioning
confidence: 99%